Sealing ability of Biodentine versus ProRoot mineral trioxide aggregate as root-end filling materials - Mohamed Nabeel; Hossam M. Tawfik; Ashraf M.A. Abu-Seida; Abeer A. Elgendy (Elsevier, 2019)
Aim: This study evaluated the sealing ability of ProRoot MTA and Biodentine as root-end filling materials. Method: In total, twenty (N = 20) extracted human maxillary central incisor teeth were decontaminated, cleaned and decoronated. Instrumentation was performed according to the step back technique using #50 Flex-o-file. Then the canals were flared to #70 Flex-o-file. Obturation was performed with conventional gutta percha and a resinous sealer (AH26) using the lateral condensation technique. Resection of 3 mm of apical end of each root was achieved perpendicular to the long axis of the root. Root-end cavity was prepared in each sample ultrasonically then filled with tested materials (N = 10). Fluid filtration method was used to assess the sealing ability of each tested material at three different experimental periods; one day, one week and one month after setting. All data were tabulated and statistically analyzed with a level of significance set at P ≤ .05. Results: At each specific time interval, the leakage mean values were not consistent among the tested materials. At one day interval, ProRoot MTA samples had a higher leakage mean value than Biodentine samples. However, this difference in leakage was not statistically significant (P > .05). At one week interval, both materials showed an increased degree of leakage mean value with no significant difference (P > .05). At one month interval, ProRoot MTA samples showed a decrease in leakage mean value, while the Biodentine samples showed a further increase in leakage mean value. This difference was statistically significant (P < .05). Conclusion: Although the sealing ability of ProRoot MTA is superior to Biodentine, Biodentine could be considered as an acceptable alternative to ProRoot MTA in peri-radicular surgeries. Keywords: Endodontic failure, Endodontic treatment, Fluid filtration method, Periapical pathosis, Root-end cavity preparations, Surgical endodontic